2017
DOI: 10.1109/tsp.2017.2723348
|View full text |Cite
|
Sign up to set email alerts
|

A Multisensor Multi-Bernoulli Filter

Abstract: In this paper we derive a multi-sensor multi-Bernoulli (MS-MeMBer) filter for multi-target tracking. Measurements from multiple sensors are employed by the proposed filter to update a set of tracks modeled as a multi-Bernoulli random finite set. An exact implementation of the MS-MeMBer update procedure is computationally intractable. We propose an efficient approximate implementation by using a greedy measurement partitioning mechanism. The proposed filter allows for Gaussian mixture or particle filter impleme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 19 publications
0
65
0
Order By: Relevance
“…Random finite sets, generalized labeled multi-Bernoulli, multi-object tracking, data association, Gibbs sampling The classical PHD and CPHD filters are developed for single-sensors. Since the multi-sensor PHD, CPHD and multi-Bernoulli filters are combinatiorial [4], [30], the most commonly used approximate multi-sensor PHD, CPHD and multi-Bernoulli filter are the heuristic "iterated corrector" versions [31] that apply single-sensor updates, once for each sensor in turn. This approach yields final solutions that depend on the order in which the sensors are processed.…”
Section: Index Termsmentioning
confidence: 99%
See 1 more Smart Citation
“…Random finite sets, generalized labeled multi-Bernoulli, multi-object tracking, data association, Gibbs sampling The classical PHD and CPHD filters are developed for single-sensors. Since the multi-sensor PHD, CPHD and multi-Bernoulli filters are combinatiorial [4], [30], the most commonly used approximate multi-sensor PHD, CPHD and multi-Bernoulli filter are the heuristic "iterated corrector" versions [31] that apply single-sensor updates, once for each sensor in turn. This approach yields final solutions that depend on the order in which the sensors are processed.…”
Section: Index Termsmentioning
confidence: 99%
“…Instead of sampling from π(I + , θ + |I, ξ) ∝ ω (I,ξ,I+,θ+) Z+ , this subsection introduces an alternative target distribution for the Gibbs sampler, which can drastically reduce the complexity. Unique samples from the alternative target distribution are then reweighted according to (30).…”
Section: B Alternative Target Distributionmentioning
confidence: 99%
“…However, it has been reported that the estimation results depend on the order in which the RDs are processed [36]. An alternative way to mitigate the computational load is to directly reduce the number of partitions and associations in each partition [33], [34], [37]- [39]. In [37], a distance partition method is proposed for extended target tracking.…”
Section: Introductionmentioning
confidence: 99%
“…Then, by applying the l max partition to the partitioned measurement set, the number of resulting partitions can be further reduced. In [38], [39], a greedy partition method is proposed to reduce the number of partitions. It considers only a certain number of partitions with the highest weight at every step and discards the others.…”
Section: Introductionmentioning
confidence: 99%
“…And to improve the estimation accuracy, the multiBernoulli smoother which consists of original CBMeMBer filter and backward smoothing was proposed in [11]. In addition, the multi-Bernoulli filter was also enhanced for multi-sensor tracking [12,13], extended target tracking [14,15], multipath multi-target tracking [16], and group object tracking [17].…”
Section: Introductionmentioning
confidence: 99%